Nivel de resiliencia y riesgo suicida en las pacientes de la Unidad infanto-juvenil del Instituto Psiquiátrico “Sagrado Corazón - Salazar Morales, Marco Sebastián (2018)
In Ecuador, the incidence of suicide is high in accordance with international statistics, at present also because of the tendency towards family breakdown, adolescence becomes a vulnerable population due to the experienced shortages and poor resilience. Therefore, the present investigation is directed to describe the influence of the resilience level in the suicide risk; it starts from a non-experimental cross-sectional design, applied in a non-probabilistic sample determined by inclusion and exclusion criteria, composed of twenty female adolescent patients treated in the Child-Youth Unit of the "Sacred Heart" Psychiatric Institute in Quito city. Two quantifiable instruments were used: The Wagnild and Young Resilience Scale, and the Plutchik Suicide Risk Scale, as results gotten were: 70% of adolescents show low levels of resilience, 25% average levels, and 5% high levels. Likewise, 90% of adolescents are at a tentative suicide risk, while the remaining 10% are not. In addition, the correlation analysis performed in the statistical package SPSS 24.0 showed that there is a significant correlation between the level of resilience and the presence of suicide risk. This study determining that, a lower resilience level; the risk of suicidal ideation or act in adolescents increases; this correlation being inversely applied, it proposes that when there is higher level of resilience, the suicide risk is lower.